Let’s address your questions one by one:
Question 1
Using the Negative Exponent Rule, we know that \( a^{-n} = \frac{1}{a^n} \).
So, \[ 3^{-12} = \frac{1}{3^{12}} \]
To write it in radical form, we can express the exponent as a root: \[ 3^{-12} = \frac{1}{3^{12}} = \frac{1}{\sqrt[1/12]{3^{12}}} = \frac{1}{(\sqrt[12]{3})^{12}} = \frac{1}{\sqrt[12]{3^{12}}} \]
Thus, the equivalent expression is: \[ 3^{-12} = \frac{1}{\sqrt[12]{3^{12}}} \]
Question 2
Using the Quotient Property, which states that \( \frac{a^m}{a^n} = a^{m-n} \), let's simplify \( \frac{9^3}{9^5} \):
Calculating the exponent: \[ 3 - 5 = -2 \]
So, the simplified exponent in fraction form is: \[ -2 = -\frac{2}{1} \]
Question 3
To solve for \( x \) in the equation \( x^{15} = 6 \), we can take the 15th root of both sides:
\[ x = 6^{\frac{1}{15}} \]
Question 4
To solve the equation \( 2^{x+2} = 42 \), we can rewrite it in logarithm form:
\[ x + 2 = \log_2(42) \] Now subtract 2 from both sides to solve for \( x \): \[ x = \log_2(42) - 2 \]
Question 5
To solve the equation \( 3^{x-2} = 81 \), we first rewrite \( 81 \) as a power of \( 3 \):
\[ 3^{x-2} = 3^4 \]
Setting the exponents equal, we have: \[ x - 2 = 4 \] Now, adding 2 to both sides: \[ x = 6 \]
Summary of Answers
- \( 3^{-12} = \frac{1}{3^{12}} \)
- The simplified exponent is \( -\frac{2}{1} \)
- \( x = 6^{\frac{1}{15}} \)
- \( x = \log_2(42) - 2 \)
- \( x = 6 \)